Gastronomic Experiences in Binondo of PLM Employees: Basis for Promotion of the District - Armi Nina A. Bacho; Jay Anthony A. Capistrano Jr.; Sheila Mae A. Cruz; Chezka Faith T. Reguindin and Lei Diane C. Tan. 4 0 16; 5
u
Undergraduate Thesis: (B.S. in Travel and Tourism Management) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2